Don't forget the teacher: New tools to support broader adoption of remote labs - Jona, K.; Uttal, D. (2013 10th International Conference on Remote Engineering and Virtual Instrumentation (REV), 2013)
In order to support broad adoption of remote labs in elementary and secondary schools, we need to provide powerful, easy-to-use interfaces, not just to students, but also to teachers. We are developing tools to provide richer, technology-supported representations that improve teachers' ability to visualize student remote lab activities and diagnose misconceptions with the goal of maximizing remote lab's educational value and impact.